2004
DOI: 10.1128/jb.186.22.7549-7555.2004
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus AgrA Binding to the RNAIII- agr Regulatory Region

Abstract: The control of virulence gene expression in the human pathogen Staphylococcus aureus is under the partial control of the two-component quorum-sensing system encoded by genes of the agr locus. The product of the agrA gene has been shown by amino acid sequence similarity to be the putative response regulator; however, binding of AgrA to promoters under its control has not yet been demonstrated. In this study, we isolated and purified soluble AgrA by expression under osmotic shock conditions and ion-exchange chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
186
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 27 publications
11
186
0
1
Order By: Relevance
“…Furthermore, there was a greater difference in production of PSM␣3 (5.93-fold increased for USA300 vs. USA100/USA200 infection isolates; 6.23-fold increased for USA500 infection isolates) than in that of ␦-toxin (2.35-and 2.09-fold, respectively) between USA300 and USA500 strains vs. USA100/USA200. Although both the psm␣ operon and the RNAIII-embedded ␦-toxin gene hld are under direct control of the AgrA response regulator protein (27,35), we previously found that the intergenic region in front of the psm␣ operon is subject to additional regulatory influences on psm␣ expression (27). The findings presented here are in accordance with these previous results and indicate that although agr activity plays a major role in defining the exceptional virulence potential of the USA300/USA500 sublineage, regulatory influences other than agr also have an impact on expression of key virulence determinants in these strains.…”
Section: Sequential Acquisition Of Virulence Genes By Contemporary Cc8mentioning
confidence: 99%
“…Furthermore, there was a greater difference in production of PSM␣3 (5.93-fold increased for USA300 vs. USA100/USA200 infection isolates; 6.23-fold increased for USA500 infection isolates) than in that of ␦-toxin (2.35-and 2.09-fold, respectively) between USA300 and USA500 strains vs. USA100/USA200. Although both the psm␣ operon and the RNAIII-embedded ␦-toxin gene hld are under direct control of the AgrA response regulator protein (27,35), we previously found that the intergenic region in front of the psm␣ operon is subject to additional regulatory influences on psm␣ expression (27). The findings presented here are in accordance with these previous results and indicate that although agr activity plays a major role in defining the exceptional virulence potential of the USA300/USA500 sublineage, regulatory influences other than agr also have an impact on expression of key virulence determinants in these strains.…”
Section: Sequential Acquisition Of Virulence Genes By Contemporary Cc8mentioning
confidence: 99%
“…The active AIP is 7-9 aa, with a 5-membered thiolactone ring (Roux et al, 2009). AgrC is a membrane-bound sensor kinase to which extracellular AIP binds, leading to AgrC autophosphorylation and activation of AgrA (Ji et al, 1995;Koenig et al, 2004;Lina et al, 1998). The agr system is intricately involved in the regulation of virulence genes, predominantly from two promoters, P2 and P3, which produce RNAII and RNAIII, respectively (Morfeldt et al, 1995;Novick & Geisinger, 2008).…”
Section: Quorum Sensing In Staphylococcus Aureus Virulencementioning
confidence: 99%
“…P2 promotes the transcription of the agr operon from the RNAII transcript, which includes agrA, agrB, agrC and agrD Roux et al, 2009). Active AgrA may be a phosphorylated homodimer that induces transcription at the P2 and P3 promoters, with a higher affinity for P2 (George & Muir, 2007;Koenig et al, 2004). Transcription from P3 leads to the production of RNAIII, which is the effector molecule of the agr system (Roux et al, 2009).…”
Section: Quorum Sensing In Staphylococcus Aureus Virulencementioning
confidence: 99%
“…1a). Phospho-AgrA activates the agrP3 promoter driving transcription of RNAIII that has multiple roles 30 . RNAIII functions as an mRNA that encodes δ-toxin (a membrane disrupting exo-protein that lyses eukaryotic host cells), and RNAIII also participates in regulation of other genes required for exo-toxin secretion and biofilm disassembly 31 .…”
Section: Introductionmentioning
confidence: 99%